2005
DOI: 10.1128/jb.187.23.8164-8171.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Degenerate Type III Secretion System from Septicemic Escherichia coli Contributes to Pathogenesis

Abstract: The type III secretion system (T3SS) is an important virulence factor used by several gram-negative bacteria to deliver effector proteins which subvert host cellular processes. Enterohemorrhagic Escherichia coli O157 has a well-defined T3SS involved in attachment and effacement (ETT1) and critical for virulence. A gene cluster potentially encoding an additional T3SS (ETT2), which resembles the SPI-1 system in Salmonella enterica, was found in its genome sequence. The ETT2 gene cluster has since been found in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 38 publications
(46 reference statements)
5
70
0
Order By: Relevance
“…Among the virulence-associated loci present in 7122 and IMT2125 but absent from APEC O1 is the degenerate type III secretion locus ETT2, located between yqeG and the glyU tRNA locus in many E. coli strains (63). The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30). Within ETT2, the predicted spaS and eivJ genes contain distinct frameshift mutations in 7122 and IMT2125, consistent with the varied patterns of mutational attrition of the locus reported among E. coli strains (30,63).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Among the virulence-associated loci present in 7122 and IMT2125 but absent from APEC O1 is the degenerate type III secretion locus ETT2, located between yqeG and the glyU tRNA locus in many E. coli strains (63). The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30). Within ETT2, the predicted spaS and eivJ genes contain distinct frameshift mutations in 7122 and IMT2125, consistent with the varied patterns of mutational attrition of the locus reported among E. coli strains (30,63).…”
Section: Resultsmentioning
confidence: 65%
“…The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30). Within ETT2, the predicted spaS and eivJ genes contain distinct frameshift mutations in 7122 and IMT2125, consistent with the varied patterns of mutational attrition of the locus reported among E. coli strains (30,63). The ymcDCBA-yccZ-etp-etk genes, which determine O-antigen capsule biosynthesis (located between appA and yccM) (64), were conserved in both 7122 and IMT2125 but absent in APEC O1.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Subtractive hybridization studies with an APEC O78 strain first revealed a gene of the degenerate Type III secretion system (ETT2) (Mokady et al, 2005). Subsequent work established the presence of an ETT2 cluster among APEC strains that underwent mutational attrition but remained essential for APEC virulence (Ideses et al, 2005b). In E. coli O157:H7, the cryptic ETT2 island does not function as a protein secretion system but as a regulator of other virulence determinants (Zhang et al, 2004).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…Pellicle formation in 3937 requires a functional type III secretion system (T3SS) (23). A similar phenomenon has been observed in Escherichia coli, where a degenerate T3SS is required for both virulence and bacterial aggregation (10). However, based on experiments with another plant pathogen, Ralstonia solanacearum, it does not appear that the T3SS of plant pathogens contributes to bacterial adhesion to host cells (20).…”
mentioning
confidence: 95%